Legal Certainty Against Termination of Government Goods/Services Procurement Contracts By Acts of Government Administration, Commitment Making Officials - Mochamad Arief Pratomo; Fauzie Yusuf Hasibuan; Atma Suganda (CV. Publikasi Indonesia, 2024)
Problems in unilateral contract termination by Commitment Making Officials in Government Procurement of Goods/Services. There are no express provisions in the laws and regulations or Presidential Regulations. The consequence that arises is that terminating the contract creates legal uncertainty. This dissertation analyzes the implementation of terminating contracts for the procurement of government goods/services by acts of government administration and analyzes and finds legal certainty for terminating contracts for the procurement of goods/services if there is a dispute between the Commitment Making Official and the provider of goods/services, the Commitment Making Official. The research method used in this research is normative juridical with research specifications namely analytical descriptive. The results research show that the implementation of terminating contracts for the procurement of government goods/services by the actions of the government administration officials who made the commitment resulted in the emergence of legal uncertainty. Based on Article 93 paragraph 1 of Presidential Regulation Number 4 of 2015 concerning the Second Amendment to Presidential Regulation Number 54 of 2010, the legal consequences of contract termination do not yet reflect the principle of proportionality, because the determination of sanctions is only unilateral, borne by the Service Provider. Meanwhile, the determination of sanctions against Service Users if the PPK commits an error/negligence is not clearly regulated either in the contract agreed upon by the parties, or regulated in the provisions of statutory regulations.